(untitled) (Journal of Hama University, 2022)
This research was conducted in the laboratories of the National commission for Biotechnology in 2020-2021. And aimed to study the chemical and the effect of adding salt, sugar and different pH levels in the gum extracted from the prickly pear (Opuntia ficus-indica) cladodes and Arabic gum. The cactus cladodes samples was collected and prepared for the extraction process, The gum was extracted and deposited by ethanol and dried, the percentage of moisture, ash, fat, protein and carbohydrates of Opuntia ficus-indica cladodes gum was 11.04%, 28.45%, 0.39%, 6.45% and 52.95%. Respectively, and 10.37%, 3.48%, 0.28%, 1.64% and 75.36% for Arabic gum.. The effect of adding sugar, salt, and different pH levels in the viscosity of both gums was studied, and it was found that adding sugar causes an increase in the viscosity of Arabic gum and Opuntia ficus-indica cladodes gum, while adding salt reduced the viscosity of both gums, the decrease was gradual for Arabic gum, but the increase in salt concentration did not cause any significant effect In reducing the viscosity of Opuntia ficus-indica cladodes gum. The pH levels affected both gums.